Political hypocrisy : the mask of power, from Hobbes to Orwell and beyond - Runciman, David (Princeton University Press, 2008)
What kind of hypocrite should voters choose as their next leader? The question seems utterly cynical. But, as David Runciman suggests, it is actually much more cynical to pretend that politics can ever be completely sincere. The most dangerous form of political hypocrisy is to claim to have a politics without hypocrisy. Political Hypocrisy is a timely, and timeless, book on the problems of sincerity and truth in politics, and how we can deal with them without slipping into hypocrisy ourselves.